Metabolomics Reveal d-Alanine:d-Alanine Ligase As the Target of d-Cycloserine in Mycobacterium tuberculosis - Prosser, Gareth A. (American Chemical Society, 2013)
[Image: see text] Stable isotope-mass spectrometry (MS)-based metabolomic profiling is a powerful technique for following changes in specific metabolite pool sizes and metabolic flux under various experimental conditions in a test organism or cell type. Here, we use a metabolomics approach to interrogate the mechanism of antibiotic action of d-cycloserine (DCS), a second line antibiotic used in the treatment of multidrug resistant Mycobacterium tuberculosis infections. We use doubly labeled (13)C α-carbon-(2)H l-alanine to allow tracking of both alanine racemase and d-alanine:d-alanine ligase activity in M. tuberculosis challenged with DCS and reveal that d-alanine:d-alanine ligase is more strongly inhibited than alanine racemase at equivalent DCS concentrations. We also shed light on mechanisms surrounding d-Ala-mediated antagonism of DCS growth inhibition and provide evidence for a postantibiotic effect for this drug. Our results illustrate the potential of metabolomics in cellular drug-target engagement studies and consequently have broad implications in future drug development and target validation ventures.